2019
DOI: 10.1111/ejh.13362
|View full text |Cite
|
Sign up to set email alerts
|

HbS/β+ thalassemia: Really a mild disease? A National survey from the AIEOP Sickle Cell Disease Study Group with genotype‐phenotype correlation

Abstract: Objectives HbS/β+ patients’ presence in Italy increased due to immigration; these patients are clinically heterogeneous, and specific guidelines are lacking. Our aim is to describe a cohort of HbS/β+ patients, with genotype‐phenotype correlation, in order to offer guidance for clinical management of such patients. Methods Retrospective cohort study of HbS/β+ patients among 15 AIEOP Centres. Results A total of 41 molecularly confirmed S/β+ patients were enrolled (1‐55 years, median 10.9) and classified on β+ mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…By contrast, Sβ+ and SC are rarer genotypes and usually initially present with less severe anemia and infrequent vaso-occlusive crises in childhood. Over time, patients with these subtypes often gradually develop multiple complications such as stroke, avascular necrosis of bones requiring joint replacement, sickle cell retinopathy, and hepatosplenic sequestration [6][7][8]. Due to their gradual clinical progression, these rarer subtypes may be misunderstood and remain undiagnosed for years, such as in this case.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By contrast, Sβ+ and SC are rarer genotypes and usually initially present with less severe anemia and infrequent vaso-occlusive crises in childhood. Over time, patients with these subtypes often gradually develop multiple complications such as stroke, avascular necrosis of bones requiring joint replacement, sickle cell retinopathy, and hepatosplenic sequestration [6][7][8]. Due to their gradual clinical progression, these rarer subtypes may be misunderstood and remain undiagnosed for years, such as in this case.…”
Section: Discussionmentioning
confidence: 97%
“…Ischemic stroke is a well-established complication of SCD, with a recent study suggesting an incidence rate of approximately 2% in children and young adults [10]. While the existing literature suggests that the overall risk of stroke is lower among Sβ+ patients, it still represents a significant source of morbidity [6][7][8]. This is evident in the patient described in this report, who continues to have gait problems and imbalance, expressive aphasia, and cognitive impairment requiring her mother to oversee her overall care.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Notarangelo et al [12] , HbS/β patients with confirmed molecular accuracy were classified according to the β mutation, and it was reported that some mutation differences with IVS-I-5 (G>C), IVS-I-5 (G>A) and IVS-I-110 had a more severe phenotype and clinical presentation, and some mutation differences were associated with a milder phenotype [8] . The study by Belisário et al [22] reported that the newly discovered 92 (C>T) and IVS-II-844 (C>A)/IVS-II-839 (T>C) mutation presented as a very mild HbS/β+ case.…”
Section: Discussionmentioning
confidence: 99%
“…It may cause serious and life-threatening complications [13] [14] . Patients who were admitted to a hospital with complaints of stroke and sequestration were reported [12] [27] . Sequestration crisis is seen in HbSS or HbSβ 0 cases before the age of 5, while, in HbS/β cases, it may delay until puberty and early adulthood and progress rapidly, resulting in death as a result of hypovolemic shock [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation